Real-time motion and magnetic field correction for GABA editing using EPI volumetric navigated MEGA-SPECIAL sequence: Reproducibility and Gender effects - Saleh, Muhammad G (Department of Human Biology, 2017)
γ-aminobutyric acid (GABA) is the primary inhibitory neurotransmitter and is of great interest to the magnetic resonance spectroscopy (MRS) community due to its role in several neurological diseases and disorders. Since GABA acquisition without macromolecule contamination requires long scan times and strongly depends on magnetic field (B0) stability, it is highly susceptible to motion and B0 inhomogeneity. In this work, a pair of three-dimensional (3D) echo planar imaging (EPI) volumetric navigators (vNav) with different echo times, were inserted in MEGA-SPECIAL to perform prospective correction for changes in the subject's head position and orientation, as well as changes in B0. The navigators do not increase acquisition time and have negligible effect on the GABA signal. The motion estimates are obtained by registering the first of the pairs of successive vNav volume images to the first volume image. The 3D field maps are calculated through complex division of the pair of vNav contrasts and are used for estimating zero- and first-order shim changes in the volume of interest (VOI). The efficacy of the vNav MEGA-SPECIAL sequence was demonstrated in-vitro and in vivo. Without motion and shim correction, spectral distortions and increases in spectral fitting error, linewidth and GABA concentration relative to creatine were observed in the presence of motion. The navigated sequence yielded high spectral quality despite significant subject motion. Using the volumetric navigated MEGA-SPECIAL sequence, the reproducibility of GABA measurements over a 40 minute period was investigated in two regions, the anterior cingulate (ACC) and medial parietal (PAR) cortices, and compared for different analysis packages, namely LCModel, jMRUI and GANNET. LCModel analysis yielded the most reproducible results, followed by jMRUI and GANNET. GABA levels in ACC were unchanged over time, while GABA levels in PAR were significantly lower for the second measurement. In ACC, GABA levels did not differ between males and females. In contrast, males had higher GABA levels in PAR. This gender difference was, however, only present in the first acquisition. Only in males did GABA levels in PAR decrease over time. These results demonstrate that gender differences are regional, and that GABA levels may fluctuate differently in different regions and sexes.